Efficient design of a reversible 2-to-4 decoder in quantumdot cellular automata using Toffoli gates - Galadima, Bahijja Yahaya; Shehu Musa Galadanci, Garba; Muhammad Shehu, Nura (International Journal of Engineering and Technology, 2024)
This research presents an optimized design of a 2-to-4 decoder in Quantum-dot Cellular Automata (QCA) using a new formula developed from the Reversible logic. The proposed QCA decoder architecture employs 112 cells and occupies an area of 0.13μm², achieving a significant reduction in size compared to previous designs. The circuit is designed using a single-layer approach, enhancing its efficiency and minimizing power dissipation. Simulation results using the QCA Designer simulator version 2.0.3 demonstrate the enhanced functionality of the suggested decoder in regard to functionality and also efficiency, making it a promising candidate for future nanoscale integrated circuit applications.